2022
DOI: 10.1002/14651858.cd009261.pub7
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy for surgical wounds healing by primary closure

Abstract: Background Indications for the use of negative pressure wound therapy (NPWT) are broad and include prophylaxis for surgical site infections (SSIs). Existing evidence for the effectiveness of NPWT on postoperative wounds healing by primary closure remains uncertain. Objectives To assess the effects of NPWT for preventing SSI in wounds healing through primary closure, and to assess the cost‐effectiveness of NPWT in wounds healing through primary closure. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 231 publications
0
51
0
5
Order By: Relevance
“…Authors of a metaanalysis of 23 RCTs involving 2547 patients undergoing various surgical procedures (eg, abdominal, cesarean delivery, orthopedic, vascular) concluded that use of incisional negative pressure wound therapy for primary wound closure was associated with lower rates of surgical site infection than use of standard dressings: 9.7% (124 of 1279) vs 15% (191 of 1268; RR, 0.67 [95% CI, 0.53-0.85]; P < .001); however, the effect varied by procedure type. 69 The authors indi-cated that they did not find evidence for substantial differences between the different types of surgery. Similarly, authors of a recent meta-analysis of 28 RCTs concluded that incisional negative pressure wound therapy was associated with lower rates of surgical site infection than standard dressing: 8.8% (194 of 2193) vs 14% (315 of 2205; RR, 0.61 [95% CI, 0.49-0.76]; P < .001).…”
Section: Postoperativementioning
confidence: 97%
“…Authors of a metaanalysis of 23 RCTs involving 2547 patients undergoing various surgical procedures (eg, abdominal, cesarean delivery, orthopedic, vascular) concluded that use of incisional negative pressure wound therapy for primary wound closure was associated with lower rates of surgical site infection than use of standard dressings: 9.7% (124 of 1279) vs 15% (191 of 1268; RR, 0.67 [95% CI, 0.53-0.85]; P < .001); however, the effect varied by procedure type. 69 The authors indi-cated that they did not find evidence for substantial differences between the different types of surgery. Similarly, authors of a recent meta-analysis of 28 RCTs concluded that incisional negative pressure wound therapy was associated with lower rates of surgical site infection than standard dressing: 8.8% (194 of 2193) vs 14% (315 of 2205; RR, 0.61 [95% CI, 0.49-0.76]; P < .001).…”
Section: Postoperativementioning
confidence: 97%
“…Research on patients’ experiences of iNPWT for the treatment of closed wounds is scarce and there is a high demand for qualitative studies supplementing the quantitative RCTs ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 , 4 , 9 Negative wound pressure therapy (NWPT) is recommended by some authors when skin grafting is being considered, 9 and the majority of articles on DDH mention the use of NWPT, 3 , 10 – 12 despite the low level of evidence supporting its value. 13 , 14 Post-operative wound management was limited to local care and dressings in only two reported DDH cases. 6 , 15 In our case, rapid healing deemed skin grafting unwarranted, so NWPT was not proposed.…”
Section: Discussionmentioning
confidence: 99%